THE TENSILE PROPERTIES OF HOT-ROLLED (AL2O3)(P)-AL COMPOSITES - LEE, JC; SUBRAMANIAN, KN (ELSEVIER SCIENCE SA LAUSANNE, 1995)
Hot rolling was carried out on the extruded Al alloy 6061 composite reinforced with Al2O3 particulates ((Al2O3)(p)-Al composite) along a direction perpendicular to the extrusion direction of the composite. Room-temperature tensile tests of the hot-rolled composites showed a significant increase in strength and fracture strain along the transverse (rolling) direction with increasing reduction in rolling. However, the same properties along the longitudinal (extrusion) direction were relatively unaffected by hot rolling. Such behaviors of rolled composites are compared with those of the cold-rolled composites and analyzed on the basis of the microstructural changes such as redistribution of the particulate clusters, disappearance of the particulate-free zones, particulate damage and smaller matrix grain size of the rolled composites.
Keywords: MATRIX COMPOSITES; REINFORCEMENT; ALUMINUM